RIPPLE MARKS—The Story Behind the Story - Cheryl Lyn Dybas (Oceanography, 2014)
It's September. Seafood restaurants from coast to coast are serving platter after platter of steaming crabs, ready for hammering and picking. The supply seems endless, but is it?